Review of leaf beetles from the genus Entomoscelis (Coleoptera: Chrysomelidae) in Kazakhstan and Central Asia - Mikhailov, Yuri E. (Zootaxa, 2019)
From the leaf beetle genus Entomoscelis only E. adonidis (Pallas) has been reliably recorded for Kazakhstan and major parts of Central Asia so far. Distribution of E. adonidis is first mapped in Kazakhstan in connection to natural zonation. Besides, the records of this species in Central Asia are summarized, southern and south-eastern borders of its distribution area are first clearly demonstrated. E. pilula Lopatin described from Azerbaijan and hitherto known only from the Caucasus is first recorded from Western Kazakhstan. E. sacra is recorded from South Kazakhstan and for the first time from South Urals in Russia and Ukraine. The identity of E. sacra is discussed. A key is provided for the Entomoscelis species from Kazakhstan and Central Asia. Trans-Caspian type of distribution of E. pilula is discussed from a zoogeographical point of view.